GAYA HIDUP LANSIA YANG MENGALAMI HIPERTENSI DI UPT PELAYANAN SOSIAL LANJUT USIA WILAYAH BINJAI-MEDAN TAHUN 2014 - novita, debi (UNIVERSITAS SARI MUTIARA INDONESIA, 2016)
UPT (Integrated Service Unit) of elderly people social sevice in Binjai-Medan area is a North Sumatra government- owned nursing home at Binjai. A preliminary survey showed that of the 180 elderly people in this nursing home, 167 of them (92.78%) of the suffered from hypertension . The objective of the research was to analyze the life style of elderly people suffered from hypertension with the indicators of eating pattern; smoking habit; physical activity; and rest and sleep pattern. The research used qualitative method with case study strategy. The data ware gathered by conducting in-depth interview, then in analysis based on themes obtained from interview. Informan in this research is elderly people who suffered hypertension. The results of the research showed that the elderly in the nursing home had generally complied with the rules on healthy life style although, in reality, some of them still disobeyed health lifestyle at the indicators of eating pattern such as buyimg and eating outside at will, adding salt and menu to their food and drank coffee; at the indicators of smoking habit it was found that some of them still smoked because they thought that could remove pain like toothache, headache, and old habit; at the indicator of physical activity it was found that many of them only did routine physical activity , and some of them only did gardening and selling; at the indicator of rest and sleep pattern it was found that some of them were distrubed by something ringing in their ears, some of them were noisy, and some of them were difficult to fall asleep. It is recommended that the UPT management pay more attention to the elderly people’s daily activitiies by increasing the elderly ppeople’s service activities, especially cuonseling about healthy lifestyle, getting together, and skill so that the elderly people in the nursing home can live healthily.